UPAYA MENINGKATKAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) PESERTA DIDIK KELAS VII.8 SMP NEGERI 16 PALEMBANG - Marlinda, Marlinda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose to be achieved in this study is to improve student learning outcomes in PKn lessons in class VII.8 students of SMP Negeri 16 Palembang by using a cooperative model type Think Pair Share (TPS). So the problem in this research is how to increase the learning outcomes of students in class VII.8 of SMP Negeri 16 Palembang through a Think Pair Share learning model? Based on the results of the research stated in the previous chapter, the conclusions that can be taken in this study are the cooperative learning type Think Pair Share (TPS) model which has a positive impact on improving PKn learning outcomes of students in class VII.8 Palembang State Middle School 18 increased learning completeness of students in each cycle, namely pre-cycle, cycle I and cycle II respectively 46.15%, 69.23% and 88.46%. The application of the cooperative learning model of the Think Pair Share (TPS) type has a positive influence, which can improve student learning outcomes as indicated by the average answers of students who state that students are interested and interested in the cooperative learning model type Think Pair Share (TPS) so they become motivated to learn.